The protective effect of vitamin D against carbon tetrachloride damage to the rat liver - Ozerkan, D.; Guney, Şevin; Ozturk, G.; Ozsoy, N.; Akbulut, Kazime Gonca (Informa UK Limited, 2017)
We investigated the protective effect of vitamin D against liver damage caused by carbon tetrachloride (CCl4). Twenty-four male rats were divided into four equal groups: G1, untreated controls; G2, administered CCl4; G3, administered both CCl4 and vitamin D for 10 weeks; G4, administered CCl4 for 10 weeks and vitamin D for 12 weeks. At the end of experiment, intracardiac blood samples were taken and liver samples were removed. Hepatic damage due to CCl4 was assessed using biochemistry and histopathology. Glutathione (GSH) levels decreased, while malondialdehyde (MDA) levels increased in liver tissues of G2. Alanine transaminase (ALT), alkaline phosphatase (ALP), and gamma-glutamyl-transaminase (GGT) levels increased, while albumin (ALB) levels decreased. Hepatocyte degeneration, lobular disorder, sinusoid dilation, focal necrotic areas, hyperemia, and glycogen loss were observed. Hepatic fibrosis was observed around portal areas and central veins. Bridging fibrous septa were formed between portal veins. By immunohistochemistry, both matrix metalloproteinase-9 (MMP-9) and desmin reactivity were increased. All aspects of liver damage were at least partially prevented in rats treated with vitamin D. Vitamin D appears to act as an antioxidant and anti-fibrotic to protect the rat liver against damage.
Keywords: Male; Reverse Transcription; Reference Standards; Immunohistochemistry; Polymerase Chain Reaction; Rats; Liver; Animals; Rats, Wistar; Vitamin D; Carbon Tetrachloride; 3. Good health; 10. No inequality